Предмет: Алгебра, автор: dankook

Решите уравнение (x^2-3x-4) ^2 +2(x-5)(x+2)+12=0

Ответы

Автор ответа: matilda17562
3
Решение:
 ( x^{2} - 3x - 4) ^{2}  + 2*(x - 5)* (x + 2) + 12 = 0
( x^{2} - 3x - 4) ^{2} + 2*( x^{2}  - 3x - 10) + 12 = 0
( x^{2} - 3x - 4) ^{2} + 2*( (x^{2} - 3x - 4) - 6) + 12 = 0
( x^{2} - 3x - 4) ^{2} + 2* (x^{2} - 3x - 4) -  2*6 + 12 = 0
( x^{2} - 3x - 4) ^{2} + 2* (x^{2} - 3x - 4) = 0
Пусть x^{2} - 3x - 4 = t, тогда 
  t^{2}  + 2t = 0
t = 0 илиt = - 2
Получили, что 
1) x^{2} - 3x - 4 = 0 или 2) x^{2} - 3x - 4 =  -2
Решим отдельно каждое получившееся уравнение:
(1):x^{2} - 3x - 4 = 0, D = 25,  x_{1}  = 4,  x_{2}  = - 1
(2): x^{2} - 3x - 4 = - 2, x^{2} - 3x - 2 = 0, D = 17,  x_{1}  =  \frac{3 +  \sqrt{17} }{2}  ,  x_{2}  =  \frac{3 -  \sqrt{17} }{2}
Ответ:
-1; 4; \frac{3 - \sqrt{17} }{2}, \frac{3 + \sqrt{17} }{2}.



Похожие вопросы
Предмет: Биология, автор: фыва5